Financial Statement Fraud Analysis on State-Owned Entreprises in Hexagon Fraud Perspective - Nuristya, Emma Rani; Kuntari, Yeni (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This research examines fraudulent financial statements in state-owned entreprises listed on the IDX for the 2020-2022 periods. This research adopts the hexagon theory influence fraudulent financial statements in an institution. This research shows that two of the six elements, namely capability and rationalization, have a significant effect on fraudulent financial statements. The impact is positive, confirming the proposition of the hexagon theory.. The findings in this research show that there are three variables that can detect fraud in financial statements, namely CEO duality, Change in Auditor and CEO Picture. It means that dual CEO ownership and the company's desire to change its auditor indicate fraudulent financial statements, as well as the large number of CEO photos appearing in financial reports shows a high level of arrogance and superiority within the company. High arrogance can lead to fraud.